“I’m cantonese but I speak hokkien” : a case study of a Chinese Singaporean family. - Ng, Li Yan. (2013)
The purpose of this study was to investigate dialect usage and attitudes towards dialects – more specifically, the reasons for only certain dialects being passed down from generation to generation and the extent to which this might be an effect of Singapore’s Speak Mandarin Campaign (SMC). A case study was carried out by conducting semi-structured interviews with members of one particular family in which both children are proficient in only one of their inherited dialects – Hokkien. It was found that one of the main language ideologies determining language use within this family was the belief that language is a tool used for purely pragmatic purposes. While acknowledging that dialects constitute part of their ethnic identity, cultural roots and ancestry, participants highlighted the useful aspects of (some) dialects and acknowledged that Mandarin is a practical language to be proficient in. The utilitarian ideology behind the SMC was found to have influenced language use by promoting the evaluation of languages based on pragmatic value. Although it has not completely purged dialect usage from this family, the SMC can be said to have had a substantial influence particularly on the younger generation who identified far less with dialect groups than their parents did.